CEMARAN PESTISIDA FOSFAT-ORGANIK DI AIR DANAU BUYAN BULELENG BALI - I. B. Putra Manuaba (Jurnal Kimia (Journal of Chemistry), 2008)
Pesticide is a chemical used to destroy or to control any pest that damages plant, animal, etc. Therefore,pesticide is very important for protecting plant, animal, and in controlling vector-borne diseases. The use of pesticideis therefore inevitable. A study to investigate the organophosphate pesticide residue in water of Lake Buyan wascarried out.This is an expost facto study with Analytical Cross Sectional Study design. Sample preparation for thispurposed was carried out following a standard method. Gas chromatography was employed in order to gain theorganophosphate pesticide contaminant.Organophosphate pesticide contaminant, i.e. dimethoate, chlorphyrifos and prophenofos were observed on55 water sampling point taken from 5 zone. The residual contaminant of dimethoate; chlorphyriphose; andprophenophose, were 9.3, 3.5, and 2.1 ppb respectively. Total residual contaminant was 14.9 ppb which was bellowthreshold concentration of 100 ppb (SK Gubernur Bali No. 515 Tahun 2000).